Nocebo effects on motor performance: A systematic literature review - Horváth, Áron; Köteles, Ferenc; Szabo, Attila (Scandinavian journal of psychology, 2021)
Directionally opposite to placebo effects are the nocebo effects that negatively impact people’s thoughts, feelings, and actions. An important but scarcely studied aspect of everyday functioning is motor performance, in which nocebo effects might impair athletic skills and the much‐needed purposeful daily movements and motor actions. The aim of this literature review is to unveil the nocebo effects on motor performance. Searched databases were PubMed, PsycINFO, and SPORTDiscus. Twenty‐one articles, reporting 23 studies, met the eligibility criteria for inclusion in the current review. All reports exhibited “some” risk of bias. Of the 23 studies, 14 found a nocebo effect on motor performance, equivocal results emerged from two studies, and negative findings were reported in seven studies. Most (10/12) studies using a between‐subjects design have reported a nocebo effect. The mean effect size was 0.60, suggesting a medium‐to‐large effect of nocebo intervention on motor performance. Based on this review, we conclude that nocebo effects do influence motor performance and can be evoked with negative verbal information. This effect may be more robust than the placebo effect but also depends on the type of motor performance, on the examined sample, and on the nocebo agent. Hence, nocebo effects should be recognized and controlled in empirical research on motor performance, and they should be prevented or extinguished in practical and therapeutic settings. More extensive examination of the nocebo effect on motor performance is warranted, especially using between‐subjects research design and a “no agent” control condition.